Outcome versus process value in service delivery. Issue 6 (12th September 2016) - Luu, Ngoc; Hau, Le Nguyen; Ngo, Liem Viet; Bucic, Tania; Cuong, Pham Hung
Abstract : Purpose: This study is embedded in social exchange and transaction cost theories. The purpose of this paper is to compare the relative importance of process value and outcome value in building affective and cognitive relationship strength and to compare the relative effects of each type of relationship strength on attitudinal and behavioral loyalty. Design/methodology/approach: This empirical study features a quantitative approach. The sample comprises 167 business-to-business (B2B) customers of a large transportation and logistics company in Vietnam. Findings: Process value and outcome value have different effects on affective relationship strength. The effect of process value is greater than that of outcome value. In addition, cognitive strength has a stronger impact on both attitudinal and behavioral loyalty than affective strength. Research limitations/implications: These insights extend extant literature regarding the process and outcome components of the service assessment. Further studies also should use a cross-industry, cross-country sample to examine the potential moderating effects of country- or industry-specific factors. These findings show B2B managers how to make appropriate resource allocation and investment decisions to enhance relationship strength and resulting customer loyalty. Originality/value: To clarify the links among customer value, relationship strength and customer loyalty, this study examines the relative importance of rational and non-rational factors (i.e. process value vs outcome value and affective strength vs cognitive strength) for relationship performance. Unlike most prior research, this study is set in the B2B context of a developing country.